The influence of landscape on housing price: a study on gated and guarded housing schemes - Lee, Ee Leong Mark (2024)
In the world with swift variations in the economic, social, and technological advancement, the homebuyer and the proprietorship of residential housing had been rehabilitated and differentiated from the basic users to a user which factoring many considerations when purchasing the property. Homebuyers are willing to pay more premium for attractive landscapes and views. However, there is a present of research gap where there is no study that factors the characteristics of Gated and Guarded Schemes in Malaysia. As such, this study explores the amenities values contributed by these landscape and scenic view features towards the housing price using the Hedonic Pricing Model. In particular, this study will be emphasized on how landscape attributes is measured and how it contributes to the housing price. The Hedonic Pricing Model are performed using the Multiple Regression Analysis (MRA) based on a detailed fieldwork and study on 1012 landed Gated and Guarded residential properties transacted between 2015 to 2023 in a residential district. Landscape and scenic view attributes are measured from several dimensions such as duration, walking distance and radius to landscape and visibility of scenic view. This paper describes how such dataset modelled and compared. Different models were built to study on the effect of landscape toward the housing price based on different measurement of distance to landscape. The results suggested that there would be implicit prices on the landscape and scenic view can be extracted from housing price based on the different measurement of distance to landscapes and visibility of scenic views being measured. Finally, the results shown that the landscape and scenic views are multidimensional in influencing housing price. To illustrate, distance to landscape would possess negative relationship with the housing price, where the visibility of scenic view would possess positive relationship with the housing price. These results indicated the crucial of environment amenities towards the housing price. A good understanding of the impact of these variables is important for the landscape planning decisions and the valuation of Gated and Guarded Community. This study concludes by commenting upon the important of including landscape and scenic views amenities in the Hedonic Pricing Model and considers the main limitation in a wider range of study.